EFFECT OF HUMAN IMMUNODEFICIENCY VIRUS INFECTION AND COMBINATION ANTIRETROVIRAL THERAPY ON TELOMERE LENGTH - Bukić, Ena; Milasin, Jelena; Dragovic, Gordana (Medicinski podmladak, 2024)
Introduction: Due to combination antiretroviral therapy (cART), human immunodeficiency virus (HIV) infection has been transformed into a chronic disease. Despite effective therapy, the virus continues to replicate in the body. Chronic inflammation caused by the constant presence of the virus and cumulative toxicity caused by the therapy lead to changes in the body, potentially associated with an accelerated aging process. Objective: The objective of this paper was to review and analyze the most common mechanisms by which HIV infection and cART can affect telomere length. Material and Methods: This review used targeted searches of the MEDLINE and PubMed bibliographic databases using the keywords "telomeres", "telomere length", "telomere attrition", "aging" and "cellular senescence" in combination with the words "HIV", " HIV infection", "antiretroviral", "cART" and "HAART". Results: HIV-infection-related parameters affecting telomere shortening are the presence of viral Tat protein in the cell, oxidative stress, comorbidities and aberrant methylation. Drugs within cART that stand out as important for telomere shortening are efavirenz, tenofovir and dolutegravir. Conclusion: Tat and Vpr proteins, oxidative stress, DNA methylation, efavirenz administration, tenofovir administration, and dolutegravir administration can significantly affect telomere shortening in HIV-infected patients.